Metformin Effects on Pancreatic Cancer Cells - Rukaia Sheneeb; Yousef Hasen; Asia Fleafla; Ahmed Al bakoush; Wafa ALallam (AlQalam Journal of Medical and Applied Sciences, 2022)
Background and aims. Pancreatic cancer is one of the most common causes of cancer related deaths around the world. A number of transcription factors and cytokines are associated with pancreatic cancer formation. These proteins play a momentous role in the inflammatory response that may end in cancer formation. Metformin, an oral antidiabetic agent from the biguanide class has been reported to possess significant antitumor and anti-inflammatory activities. The present study was conducted to investigate the effects of this medication on pancreatic intraepithelial neoplasias and pancreatic ductal adenocarcinoma cells. Methods. We worked with pancreatic intraepithelial neoplasias (PanIN) and pancreatic ductal adenocarcinoma (PDAC) cell lines, which have a characteristic K-Ras, and p53 mutation. In order to determine the effect of metformin on expression of (TNFα, IL6, IL1β and IKKβ) genes in the two cell lines (PDAC and PanIN), 5 X105/ml cell suspensions of these cell lines were seeded into 3-wells plate. The first well was the control well i.e., untreated well and the remaining two wells were treated with 10μM of the drug (Metformin). Results. The proliferation assay results showed that the antidiabetic drug inhibits cancer cells growth in a concentration and time-dependent manner, in both pancreatic cancer cell lines. In addition, treatment with Metformin resulted in downregulation of TNFα and IKKβ genes in the PanIN cell line. However, Metformin up-regulated TNFα gene and down-regulated mRNA IKKβ in PDAC cells. Conclusion. Taken together, these findings show that Metformin possesses inhibitory and anti-inflammatory effects on pancreatic cancer cells and it may represent a novel approach to prevent or treat this kind of cancer.